The Use of Story-Based Learning Method in Improving English Writing Skills - Ismiaton, Laela; Sahuddin; Thohir, Lalu; Nurtaat, Lalu (Program Studi Pendidikan Bahasa Inggris, 2025)
This study aims to examine the effectiveness of story-based learning in enhancing English writing skills among Grade 7 students at SMP Negeri 4 Gerung. Writing, a critical productive skill in language learning, is often perceived as challenging due to its demand for clarity, coherence, and mastery of language components such as grammar and vocabulary. Many students struggle with writing due to limited practice, inadequate teaching methods, and low motivation. Story-based learning offers a potential solution by providing an engaging and context-rich environment that encourages students to develop their writing skills. This research focuses on addressing the identified challenges by utilizing stories as a medium to increase student interest and motivation. The findings showed that students in the experimental group, who were taught using story-based learning, experienced a significant improvement of 23.19% in their writing skills, as evidenced by their post-test scores. In contrast, the control group, which followed traditional teaching methods, showed only a marginal improvement of 0.79%. These results indicate that story-based learning not only enhances student engagement and interest in the learning process but also fosters creativity and critical thinking, leading to improved writing performance.